Zhuang Language: Chinese Scholars’ Perspective on Tai Language in China - Sodsonghrit, Metcha (Journal of Cultural Approach, 2015)
Chinese scholars have classified Zhuang language in Sino – Tibetan language family, Zhuang-Dong language branch. In this branch, there are three language members who have settled in Chinanamely Dai, Buyi, and Zhuang. The three languages are most closely with Thai language. This article aims to present linguistic data on the minority tribe in China, Zhuang. As perceived by Chinese scholars, this article will present two main issues: 1) Naming and resident and 2) linguistic data which consists of (1) Phonology (2) wording system (3) Grammar (4) Borrow words (5) Dialects and (6) Characters. By investigating, it revealed that although there are many Thai researchers who work on Zhuang Dictionaries, still lacking in composed of Chinese Scholars’ Perspective. This article will contribute information for Thai scholar who would like to conduct further research related to the topic in the future.